2004
DOI: 10.1530/rep.1.00176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mutations affecting gonadotropin production or responsiveness on expression of inhibin subunit mRNA and protein in the mouse ovary

Abstract: Measurement of inhibins A and B in the serum of normal cyclic rodents has implicated FSH in the regulation of these peptides within the ovary. To extend these observations we have used a panel of mutant mice carrying mutations which affect either the production of, or the ability to respond to, FSH and LH. As a consequence, the females are infertile and show different degrees of follicular development. The aim of this study was to measure inhibin gene transcription in the ovaries of these mutant females togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Likewise, elevated circulating inhibin A in tg-FSH hpg mice exhibiting antral follicle development, relative to non-tg hpg controls with antral arrest, agrees with the reported rise of inhibin A expression in secondary and antral follicles (Meunier et al 1988, Wang et al 2005. Inhibin A detection in 71% of tg-FSH (LH-deficient) hpg females in this study was similar to the 63% of LHR-null females expressing detectable inhibin A found by Hirst et al (2004). Overall, these findings support recent studies showing increased serum inhibins B and A in FSH-treated hpg females to be associated with antral follicles, although higher inhibin A requires LH activity and the presence of preovulatory follicles (Wang et al 2005).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, elevated circulating inhibin A in tg-FSH hpg mice exhibiting antral follicle development, relative to non-tg hpg controls with antral arrest, agrees with the reported rise of inhibin A expression in secondary and antral follicles (Meunier et al 1988, Wang et al 2005. Inhibin A detection in 71% of tg-FSH (LH-deficient) hpg females in this study was similar to the 63% of LHR-null females expressing detectable inhibin A found by Hirst et al (2004). Overall, these findings support recent studies showing increased serum inhibins B and A in FSH-treated hpg females to be associated with antral follicles, although higher inhibin A requires LH activity and the presence of preovulatory follicles (Wang et al 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Overall, these findings support recent studies showing increased serum inhibins B and A in FSH-treated hpg females to be associated with antral follicles, although higher inhibin A requires LH activity and the presence of preovulatory follicles (Wang et al 2005). The tg-FSH hpg ovary without LH stimulation would be expected to resemble ovaries in mice lacking functional LH-beta or receptor genes (Lei et al 2001, Zhang et al 2001, Ma et al 2004, which previously provided valuable comparisons for testicular development (Zhang et al 2001, Allan et al 2004, Hirst et al 2004. Indeed, arrested antral follicle development was observed in all these models exhibiting isolated FSH activity.…”
Section: Discussionsupporting
confidence: 83%
“…The role of FSHR in the local regulation of ovarian function has been highlighted, studying female FSHR-knockout mice. These mice are characterized by smaller ovaries, atrophic uterus and imperforate vagina [20] probably due to the lack of circulating biologically active estrogen, while their elevated serum and pituitary FSH concentrations lead to follicular arrest at the primordial, primary and preantral stages [21,22]. In the current study, the combined FSHR/SHBG/ CYP19 genotype analysis revealed increased follicle/oocytes numbers in Thr307Thr/Asn680Asn carriers compared to Ala307Ala/Ser680Ser carriers.…”
Section: Discussionsupporting
confidence: 45%
“…In the absence of FSH stimulation, follicles do not acquire LH receptors and are unable to convert thecal supplies of androgens to oestrogen. Ovarian concentrations of inhibins A and B have been found to be significantly lower in FSHβKO and FSHRKO mice compared to normal female mice and, in turn, feedback regulation of FSH is impaired.…”
Section: Discussionmentioning
confidence: 99%